On the index of stability of (r, s)-linear Weingarten Clifford tori - Lázaro Velásquez, Marco Antonio (2023)
For entire numbers r and s satisfying 0 ≤ r ≤ s ≤ n − 2, we showed that the index of (r, s)-stability of a (r, s)-linear Weingarten Clifford torus immersed into the (n + 1)-dimensional unit Euclidean sphere, that has a linear combination of their higher order mean curvatures Hr+1 and Hs+1 being null, is exactly equal to n + 3 provided that a geometric condition involving Hr+2 and Hs+2 is satisfied.